Effects of Different Relative Humidities on Flax Fibers prior to Manufacturing Their Composites Based on the Shear Response - Abdul Moudood; Anisur Rahman; Andreas Öchsner; Md Mainul Islam; Mohammad Yeakub Ali; Gaston Francucci (Advances in Materials Science and Engineering)
The moisture absorption behavior of flax fiber-reinforced epoxy composites is deliberated to be a serious issue. This property restricts their usage as outdoor engineering structures. Therefore, this study provides an investigation of moisture in flax fibers on the performance of the flax/epoxy composite materials based on their shear responses. The ±45° aligned flax fibers exposed to different relative humidities (RH) and the vacuum infusion process was used to manufacture the composite specimens. The optimum shear strength (40.25 ± 0.75 MPa) was found for the composites manufactured with 35% RH-conditioned flax fibers, but the shear modulus was reduced consistently with increasing RH values. Although shear strength was increased because of fiber swelling with increased moisture absorption rate until 35% RH environments with good microstructures, nonetheless, strength and modulus both started to decrease after this range. A very poor microstructure has been affirmed by the SEM images of the composite samples conditioned at 90% RH environments.